The Far West [videorecording (VHS)] : generous spirit - Lucas, Phil; Foulkrod, Patricia; Grant, Michael, 1954-; Geiogamah, Hanay, 1945- (Native Americans., 1994)
Explores the forces and people that shaped the northwest. Presents personal insights into the origins of the people and their cultures. Attention is given to the Kawakiutl, Lummi, Chumash, Paiute, Nez Perce.